(untitled) (Contemporary Central & East European Law, 2024)
The implementation of succession of rights in administrative proceedings raises many controversies in science and case law. The article presents key controversial issues in a comparative approach. The author defends the thesis on the effectiveness of civil law actions for rights and obligations in the sphere of public law.